2019
DOI: 10.1128/aac.00676-19
|View full text |Cite
|
Sign up to set email alerts
|

Nonnucleoside Reverse Transcriptase Inhibitor Hypersusceptibility and Resistance by Mutation of Residue 181 in HIV-1 Reverse Transcriptase

Abstract: Substitutions at residue Y181 in HIV-1 reverse transcriptase (RT), in particular, Y181C, Y181I, and Y181V, are associated with nonnucleoside RT inhibitor (NNRTI) cross-resistance. In this study, we used kinetic and thermodynamic approaches, in addition to molecular modeling, to gain insight into the mechanisms by which these substitutions confer resistance to nevirapine (NVP), efavirenz (EFV), and rilpivirine (RPV). Using pre-steady-state kinetics, we found that the dissociation constant (K d ) values for inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Concerning specific drug-classes, we found that resistance to PIs, NRTIs and NNRTIs dramatically decreased over time. However, resistance to NNRTIs has been stable at around 25% from 2011 to 2018 and NNRTI-MRMs such as Y181C, associated with wide crossresistance to NNRTIs 18,19 , remained stable at around 4%. Moreover, we found that some rilpivirine and etravirine associated mutations at position 138 of RT increased their prevalence over time, as recently observed 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning specific drug-classes, we found that resistance to PIs, NRTIs and NNRTIs dramatically decreased over time. However, resistance to NNRTIs has been stable at around 25% from 2011 to 2018 and NNRTI-MRMs such as Y181C, associated with wide crossresistance to NNRTIs 18,19 , remained stable at around 4%. Moreover, we found that some rilpivirine and etravirine associated mutations at position 138 of RT increased their prevalence over time, as recently observed 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the mutations associated with HIV resistance to nonnucleoside reverse transcriptase inhibitors, a relatively rare, nonpolymorphic V179T mutation has been shown, which is sometimes selected for in patients receiving NNRTIs. This is due to a minimal decrease in the sensitivity to etravirine and rilpivirine 29,31 . Several substitutions were also encountered at position 238: K238T, which reduces susceptibility to nevirapine and efavirenz by about 5‐fold; K238R, which is a common polymorphism that does not reduce susceptibility to NNRTIs 32 ; and K238E, a rare mutation at this position, the effect of which is not well described in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…This is due to a minimal decrease in the sensitivity to etravirine and rilpivirine. 29,31 Several substitutions were also encountered at position 238: K238T, which reduces susceptibility to nevirapine and efavirenz by about 5-fold; K238R, which is a common polymorphism that does not reduce susceptibility to NNRTIs 32 ; and K238E, a rare mutation at this position, the effect of which is not well described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we re-purchased hit compounds with IC50 values < 1.0 µM for inhibition of RT RNase H activity that were available in sufficient quantities for further analysis. We assessed their antiviral activity and cytotoxicty in TZM-bl cells, as described previously [13]. Of these compounds, only two 2) (Figure 3)), which both shared the same benzisothiazolone pharmacophore (Figure 3, red), demonstrated robust antiviral activity in the absence of cellular toxicity (Table 1).…”
Section: Identification Of Rt Rnase H Inhibitors With Antiviral Activitymentioning
confidence: 99%